2022
DOI: 10.3390/ijms23116116
|View full text |Cite
|
Sign up to set email alerts
|

APTC-C-SA01: A Novel Bacteriophage Cocktail Targeting Staphylococcus aureus and MRSA Biofilms

Abstract: The high infection and mortality rate of methicillin-resistant Staphylococcus aureus (MRSA) necessitates the urgent development of new treatment strategies. Bacteriophages (phages) have several advantages compared to antibiotics for the treatment of multi-drug-resistant bacterial infections, and thus provide a promising alternative to antibiotics. Here, S. aureus phages were isolated from patients and environmental sources. Phages were characterized for stability, morphology and genomic sequence and their bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…The P. aeruginosa phage APTC-PA18 is a lytic phage isolated from a DFU P. aeruginosa infection, which is a common occurrence, as lytic phages are frequently isolated from active infection sites in humans 19 . APTC-PA18 was shown to have desirable properties that make it an excellent clinical phage candidate as it lacked lysogeny-associated and toxin-encoding genes.…”
Section: Discussionmentioning
confidence: 99%
“…The P. aeruginosa phage APTC-PA18 is a lytic phage isolated from a DFU P. aeruginosa infection, which is a common occurrence, as lytic phages are frequently isolated from active infection sites in humans 19 . APTC-PA18 was shown to have desirable properties that make it an excellent clinical phage candidate as it lacked lysogeny-associated and toxin-encoding genes.…”
Section: Discussionmentioning
confidence: 99%
“…Titze et al (Titze and Krömker, 2020). utilized a phage mixture (7.4 × 10 9 PFU/mL) against S. aureus isolate 7142 with nuc genepositive, resulting in a reduction of bacterial colonies by 4.2 log 10 CFU/mL after 12 h. Liu et al (2022) isolated four distinct bacteriophages against drug-resistant S. aureus from various sources, namely nasal swabs, soil, and sheep feces: APTC-SA-2, APTC-SA-4, APTC-SA-12, and APTC-SA-13. Genome sequencing revealed that none of these bacteriophages contained virulence or antibiotic resistance genes.…”
Section: In Vitro Experiments Of Phage Therapy Against Drug-resistant...mentioning
confidence: 99%
“…Multiple studies have shown that isolated phages from different environmental sources exhibit high specificity towards specific bacterial strains, particularly against multidrug S. aureus [114][115][116][117][118]. Phage cocktails, composed of lytic bacteriophages individually targeting specific pathogenic strains, have shown significant results, influencing their administration [119][120][121][122][123]. A recent study demonstrated the efficacy of a potent phage cocktail named StaphLyse.…”
Section: Exploring the Potential Of Phage Therapy In Modern Medicinementioning
confidence: 99%